Fluoride release and bioactivity evaluation of glass ionomer: Forsterite nanocomposite - Fatemeh Sadat Sayyedan; Mohammadhossein Fathi; Hossein Edris; Ali Doostmohammadi; Vajihesadat Mortazavi; Farzaneh Shirani (Wolters Kluwer Medknow Publications, 2013)
Background: The most important limitation of glass ionomer cements (GICs) is the weak mechanical properties. Our previous research showed that higher mechanical properties could be achieved by addition of forsterite (Mg 2 SiO 4 ) nanoparticles to ceramic part of GIC. The objective of the present study was to fabricate a glass ionomer- Mg 2 SiO 4 nanocomposite and to evaluate the effect of addition of Mg 2 SiO 4 nanoparticles on bioactivity and fluoride release behavior of prepared nanocomposite. Materials and Methods: Forsterite nanoparticles were made by sol-gel process. X-ray diffraction (XRD) technique was used in order to phase structure characterization and determination of grain size of Mg 2 SiO 4 nanopowder. Nanocomposite was fabricated via adding 3wt.% of Mg 2 SiO 4 nanoparticles to ceramic part of commercial GIC (Fuji II GC). Fluoride ion release and bioactivity of nanocomposite were measured using the artificial saliva and simulated body fluid (SBF), respectively. Bioactivity of specimens was investigated by Fourier transitioned-infrared spectroscopy (FTIR), scanning electronmicroscopy (SEM), Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) and registration of the changes in pH of soaking solution at the soaking period. Statistical analysis was carried out by one Way analysis of variance and differences were considered significant if P < 0.05. Results: The results of XRD analysis confirmed that nanocrystalline and pure Mg 2 SiO 4 powder was obtained. Fluoride ion release evaluation showed that the values of released fluoride ions from nanocomposite are somewhat less than Fuji II GC. SEM images, pH changes of the SBF and results of the ICP-OES and FTIR tests confirmed the bioactivity of the nanocomposite. Statistical analysis showed that the differences between the results of all groups were significant (P < 0.05). Conclusion: Glass ionomer- Mg 2 SiO 4 nanocomposite could be a good candidate for dentistry and orthopedic applications, through of desirable fluoride ion release and bioactivity.